Effect of caffeine supplementation on repeated sprint running performance - Carr, A.; Dawson, B.; Schneiker, K.; Goodman, C.; Lay, B. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: This study examined the effects of 6 mg/kg caffeine ingestion in team-sport players (N.=10) on repeated-sprint running performance (5 sets of 6 ¥ 20 m) and reaction times, 60 min after caffeine or placebo ingestion. Methods: Best single sprint and total set sprint times, blood lactate and simple and choice reaction times (RT) were measured. Results: Total sprint times across sets 1, 3 and 5 (departure every 25 s) were significantly faster after caffeine (85.49±5.55 s) than placebo (86.98±5.78 s) (P<0.05). Similarly, total sprint times across sets 2 and 4 (departure every 60 s), were significantly faster after caffeine (55.99±3.64 s) than placebo (56.77±3.74 s) (P<0.05). Significantly higher blood lactates were recorded in caffeine compared to placebo after set 3 (13.1±1.2 vs 10.3±1.4 mmol·L-1) (P<0.05) and set 5 (13.1±1.3 vs 10.3±1.6 mmol/L) (P<0.01). There were no significant effects on simple or choice RT, although effect sizes suggested improved post-exercise times after caffeine. Conclusion: Caffeine ingestion 60 min prior to exercise can enhance repeated sprint running performance and is not detrimental to reaction times.